Rethinking shrinking civic space in the Global Souths – how development donors contribute to the restriction of civil society in Jordan. Issue 1 (2nd January 2023) - Sander, Alena
ABSTRACT: Traditional definitions of the shrinking space solely focus on the State's restricting role therein. They however, overlook the impact of another invested party which, especially in development contexts, plays a crucial role when it comes to civil society: Northern-based development donors. The donors' role is especially important in the case of Jordanian women's non-governmental organizations. These organizations completely depend on foreign funding and are subject to donor practice and requirements in a neo-liberal development context, while navigating the restrictive measures imposed by the neo-patriarchal Jordanian State, meant to monitor and control them in order to maintain the status quo of power relations. Based on field research in Jordan between 2017 and 2021, the study sheds light on how donor practices and State-imposed restrictive measures do not just interact, but may even reinforce each other, thereby contributing to the further narrowing of remaining civic space in Jordan.